Agrin Yes-associated Protein Promotes the Proliferation of Epicardial Cells. Issue 1 (January 2021) - Jing, Xiaodong; Liu, Bin; Deng, Songbai; Du, Jianlin; She, Qiang
Abstract : Abstract: Embryonic epicardial cells make an important contribution to cardiac development. However, their proliferation mechanism is still unclear. Epicardial cells from E12.5 fetal hearts were used in our study. Agrin was used to treat these cells. The expression of Aurora B, Ki67, and pH3 was measured by quantitative reverse transcription-polymerase chain reaction and immunofluorescence. The proportion of cells in G1/S/G2 phase was determined by flow cytometry. The results showed that agrin significantly increased the expression of ki67, pH3, and Aurora B in epicardial cells. Flow cytometry results showed that agrin significantly increased the proportion of epicardial cells in S phase. However, blocking yes-associated protein significantly downregulated the levels of ki67, pH3, and Aurora B and the proportion of epicardial cells in S phase. Thus, our results suggest that agrin may promote the proliferation of epicardial cells by regulating the yes-associated protein activity. This may be useful in exploring heart development mechanisms and preventing congenital heart disease. Abstract : Supplemental Digital Content is Available in the Text.